KEPEMIMPINAN OTOKRATIS DAN KOMPETENSI WIRAUSAHA PADA PERUSAHAAN BERBASIS KELUARGA - Ony, Johan Gunady; Rinamurti, Micheline (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
The purpose of this research is to analyze the effect of autocratic leadership and entrepreneurial competency to business performance of family company of Palembang traditional culinary’s business. The population on this research are the employee and the owner of Palembang traditional culinary’s business. Sample in this research are taken by purposive sampling method, there are 42 family company of Palembang tradisional culinary’s business. The result of this research shown that autocratic leadership and entrepreneurial competency simultanly give an influence to the business performance of family company of Palembang traditional culinary’s business. Partially, autocratic leadership do not influence the business performance and entrepreneurial competency give an influences to the business performance of family company of Palembang traditional culinary’s business.